Advances in microalgal biotechnology in Costa Rica: contributions from the Costa Rica Institute of Technology - Murillo-Vega, Francinie (2024)
Microalgal biotechnology in Costa Rica is a constantly growing field of research. The Microalgae research group of the Biotechnology Research Center (CIB) at Costa Rica Institute of Technolgy (ITCR) carries out research with microalgae in different areas, including environmental and agricultural applications, and food and biofuel development.In these fields, microalgae have been used to develop solutions to various national needs. This review addresses the main applications of microalgae in four key areas: environment, food, agriculture and bioenergy, at the national level, highlighting the contribution of this research group in the country. In addition, the challenges and opportunities that microalgal biotechnology must face for its effective integration in society and its potential to contribute to the environmental, social and economic development of Costa Rica are discussed.